Hospital mortality after hip fracture surgery in relation to length of stay by care delivery factors: A database study. Issue 16 (April 2017) - Sobolev, Boris; Guy, Pierre; Sheehan, Katie J.; Bohm, Eric; Beaupre, Lauren; Morin, Suzanne N.; Sutherland, Jason M.; Dunbar, Michael; Griesdale, Donald; Jaglal, Susan; Kuramoto, Lisa
Abstract : Abstract: Two hypotheses were offered for the effect of shorter hospital stays on mortality after hip fracture surgery: worsening the quality of care and shifting death occurrence to postacute settings. We tested whether the risk of hospital death after hip fracture surgery differed across years when postoperative stays shortened, and whether care factors moderated the association. Analysis of acute hospital discharge abstracts for subgroups defined by hospital type, bed capacity, surgical volume, and admission time. 153, 917 patients 65 years or older surgically treated for first hip fracture. Risk of hospital death. We found a decrease in the 30-day risk of hospital death from 7.0% (95%CI: 6.6–7.5) in 2004 to 5.4% (95%CI: 5.0–5.7) in 2012, with an adjusted odds ratio [OR] 0.71 (95%CI: 0.63–0.80). In subgroup analysis, only large community hospitals showed the reduction of ORs by calendar year. No trend was observed in teaching and medium community hospitals. By 2012, the risk of death in large higher volume community hospitals was 34% lower for weekend admissions, OR = 0.66 (95%CI: 0.46–0.95) and 39% lower for weekday admissions, OR = 0.61 (95%CI: 0.40–0.91), compared to 2004. In large lower volume community hospitals, the 2012 risk was 56% lower for weekend admissions, OR = 0.44 (95%CI: 0.26–0.75), compared to 2004. The risk of hospital death after hip fracture surgery decreased only in large community hospitals, despite universal shortening of hospital stays. This supports the concern of worsening the quality of hip fracture care due to shorter stays. Abstract : Supplemental Digital Content is available in the text